Soil–plant interactions modulated water availability of Swiss forests during the 2015 and 2018 droughts. (24th July 2022) - Meusburger, Katrin; Trotsiuk, Volodymyr; Schmidt‐Walter, Paul; Baltensweiler, Andri; Brun, Philipp; Bernhard, Fabian; Gharun, Mana; Habel, Raphael; Hagedorn, Frank; Köchli, Roger; Psomas, Achilleas; Puhlmann, Heike; et al.
Abstract: Central Europe has been experiencing unprecedented droughts during the last decades, stressing the decrease in tree water availability. However, the assessment of physiological drought stress is challenging, and feedback between soil and vegetation is often omitted because of scarce belowground data. Here we aimed to model Swiss forests' water availability during the 2015 and 2018 droughts by implementing the mechanistic soil‐vegetation‐atmosphere‐transport (SVAT) model LWF‐Brook90 taking advantage of regionalized depth‐resolved soil information. We calibrated the model against soil matric potential data measured from 2014 to 2018 at 44 sites along a Swiss climatic and edaphic drought gradient. Swiss forest soils' storage capacity of plant‐available water ranged from 53 mm to 341 mm, with a median of 137 ± 42 mm down to the mean potential rooting depth of 1.2 m. Topsoil was the primary water source. However, trees switched to deeper soil water sources during drought. This effect was less pronounced for coniferous trees with a shallower rooting system than for deciduous trees, which resulted in a higher reduction of actual transpiration (transpiration deficit) in coniferous trees. Across Switzerland, forest trees reduced the transpiration by 23% (compared to potential transpiration) in 2015 and 2018, maintaining annual actual transpiration comparable to other years. Together with lower evaporative fluxes, the Swiss forests did not amplify the blue water deficit. The 2018 drought, characterized by a higher and more persistent transpiration deficit than in 2015, triggered widespread early wilting across Swiss forests that was better predicted by the SVAT‐derived mean soil matric potential in the rooting zone than by climatic predictors. Such feedback‐driven quantification of ecosystem water fluxes in the soil–plant‐atmosphere continuum will be crucial to predicting physiological drought stress under future climate extremes. Abstract : Swiss early‐wilting occurrence in August 2018 (adapted after Brun et al., 2020) was best explained by mean soil matric potential in the rooting zone (ψs) and actual to potential transpiration Ta/Tp. Mean soil matric potential in the rooting zone and actual to potential transpiration in pixels with and without early wilting are significantly different and indicate early wilting thresholds.